Monitoring Seasonal Variation in Important Physio-Chemical Parameters of Arabian Seawater at Karachi Used for Feeding SWRO - Asif, Muhammad; Azmat, Rafia; Saleem, Ailyan (Asian Journal of Chemistry, 2020)
This study reports the analysis of various parameters of seawater upto 3 years used for feeding to seawater desalination (SWRO) plant at French Beach, Arabian sea, Karachi city, Pakistan. The work highlights the monitoring of essential parameters of seawater intake to reverse osmosis plant for pre-treatment loop designing and optimizing the operational cost. The study was planned as limited data was available internationally from this region, which includes pH, turbidity, temperature, total dissolved solids (TDS) and total suspended solids (TSS) allied with seasonal variations before pretreatment and after getting permeate. The water production capacity of SWRO plant is 100,000 gallon per day having Filmtech polyamide membrane and equipped with energy recovery turbine. It was observed in the period since 2015 to 2017, the monitoring of intake samples i.e. pH, turbidity and temperature showed variation in the range of 7.9-8.1, 8-34 NTU and 21-29 ºC, respectively. The observed value of TDS and TSS of seawater were 38.0-39.5 g/L and 18-48 mg/L, respectively. The concentrations of soft metals in seawater were found to be in order of Na > Mg > Ca > K while major anions were Cl− >SO42−. The TDS and pH of permeate water found to be in the range of 150-500 mg/L and 6.0-7.5 respectively, while other parameters were within WHO limit.